Never Say Sell - McMakin, Tom; Parks, Jacob (Ascent Audio, 2020)
Learn the secrets of how recurring revenue is driven at expert firms like BCG, KPMG, EY, and more Never Say Sell explains how to scale individual engagements into long-term business relationships. Cowritten by Tom McMakin, the coauthor of How Clients Buy and expert in account development, and colleague Jacob Parks, this book provides insights into how key rainmakers at firms like Accenture and IBM drive growth from existing relationships. Never Say Sell is a business development guide for professional service providers like consultants, accountants, and lawyers, whether they are sole proprietors or members of account teams tasked with expanding key accounts. Doing good work with existing clients is not enough to have them come back to you again and again. You must do more. This book explores the techniques and methods that leading professional service providers use to add value, cross sell, and drive recurring revenue from existing engagements. Never Say Sell will help you turn one-and-done clients into some of your most exciting and lucrative relationships. It is a must-have for any professional who benefits from repeat business.
Online resource; Title from title page (viewed November 17, 2020)
Keywords: Business; Affaires; businesses (business enterprises); Audiobooks